Which ESG Dimension Matters Most for Firm Value? Evidence from Indonesia - Rismawati Rismawati; Fitriani Fitriani; Muhammad Aqsa; Duriani Duriani (PT. EQUATOR SINAR AKADEMIA, 2026)
This study examines which environmental, social, and governance (ESG) disclosure dimension is most relevant to firm value in Indonesia. Using 200 firm-year observations from 50 listed firms over 2021–2024, the study estimates regression models with firm-clustered standard errors. Tobin’s Q serves as the primary firm-value proxy, while price-to-book value (PBV) is used for robustness analysis. The models control for firm size, profitability, leverage, sales growth, listing age, industry profile, and year effects, and are complemented by relative importance analysis. The results show that environmental disclosure is positively associated with Tobin’s Q at the 5% level and remains positive using PBV at the 10% level. Social and governance disclosure have positive but statistically insignificant coefficients in the full models. Relative importance analysis further indicates that environmental disclosure accounts for 65.73% of the total ESG-related explanatory contribution, compared with 25.33% for social disclosure and 8.94% for governance disclosure. Although governance disclosure is the most prevalent ESG practice in the sample, it provides the smallest incremental contribution to firm value. These findings demonstrate that ESG dimensions are not equally value-relevant and that environmental transparency provides the strongest market signal in the Indonesian context. The study extends emerging-market ESG research by combining disaggregated disclosure measures with a direct ranking of their explanatory contributions and offers practical implications for firms, investors, and regulators seeking more decision-useful sustainability reporting.